Malpractice during the Covid-19 Pandemic in Indonesia from a Medico Legal Perspective - Akhyar, Adil; Sofian, Ahmad (Universitas Muhammadiyah Purwokerto, 2026)
This article examines malpractice cases during the Covid-19 pandemic in Indonesia from a medico-legal perspective, with particular attention to the problem of causality in determining legal liability. The study employs a qualitative legal review supported by empirical case materials, statutory analysis, medico-legal literature, and relevant scholarly studies. Using a meta-synthesis approach, the article identifies how emergency health conditions, limited resources, rapidly changing medical protocols, and institutional responses during the pandemic created complex causal relationships between medical conduct, patient harm, and legal responsibility. The findings indicate that several malpractice-related incidents during the pandemic involved overlapping dimensions of criminal, civil, ethical, and administrative violations, particularly in patient treatment and the evacuation of bodies of Covid-19 patients by task force officers and medical personnel. The study argues that these cases reveal a condition of causal uncertainty, in which conventional civil liability doctrines face difficulties in proving a direct causal link between wrongful conduct and damage. Accordingly, this article proposes that Indonesian civil law should develop a more refined framework for tort liability in cases involving uncertain causation, including the possible recognition of proportional liability or causal probability-based responsibility. This refinement is essential to ensure legal protection for patients and families while maintaining fairness for medical professionals operating under public health emergency conditions.